2011
DOI: 10.1001/archoto.2010.242
|View full text |Cite
|
Sign up to set email alerts
|

Temporalis Fascia Graft Perforation and Retraction After Tympanoplasty for Chronic Tubotympanic Otitis and Attic Retraction Pockets

Abstract: Recurrent temporalis fascia graft perforation after tympanoplasty for tubotympanic otitis may be related to age and coexisting chronic sinusitis. Temporalis fascia graft retraction correlates with slower mucociliary transport time in the eustachian tube. Lateral attic wall reconstruction minimizes recurrent attic retraction in adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…Fascia graft was avoided due to poor outcome results in cases of the presence of coexisting attic retraction, as it had been shown in our previous study (13). Fascia graft was avoided due to poor outcome results in cases of the presence of coexisting attic retraction, as it had been shown in our previous study (13).…”
Section: Methodsmentioning
confidence: 68%
See 1 more Smart Citation
“…Fascia graft was avoided due to poor outcome results in cases of the presence of coexisting attic retraction, as it had been shown in our previous study (13). Fascia graft was avoided due to poor outcome results in cases of the presence of coexisting attic retraction, as it had been shown in our previous study (13).…”
Section: Methodsmentioning
confidence: 68%
“…According to our previous study, LAR itself does not decrease the incidence of postoperative retraction of the fascia graft in retracted children ears (13). In the majority of cases, LAR was performed for attic retraction.…”
Section: Discussionmentioning
confidence: 85%
“…10,11 The increased stiffness of cartilage makes it less prone to retraction and reperforation. 12,13 Initial claims about worse ABG closure using cartilage were not confirmed in a recent large meta-analysis, which showed similar audiometric outcomes compared to fascia tympanoplasty. 14 Studies have also shown the advantages of higher graft integration rate in cartilage tympanoplasty compared to temporalis fascia grafting alone.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with chronic otitis media (COM) or other diseases associated with eustachian tube dysfunction, the negative middle ear pressure increases the chance of retraction and perforation of the (replaced) TM. A recent study in a tertiary referral center population of 270 ears reported recurrent perforation in 13.9% of adults with COM undergoing TF tympanoplasty, compared to only 2.0% of adults without COM …”
Section: Introductionmentioning
confidence: 97%